A Novel Architecture of Multi-GPU Computing Card - Sen Guo; Sanfeng Chen; YongSheng Liang (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
The data transmission between GPUS in the existing multi_GPU computing card is often through PCIE which is in relative low speed, so the PCIE has become bottleneck of Overall performance. A novel architecture of multi_GPU computing card have been proposed in this paper: A multi-channel memory which have multiple interfaces is added, including one common interface shared by different GPUs, which is connected with a FPGA arbitration circuit and several other interfaces connected with dedicated GPUs frame buffer independently, and this multi-channel memory is called "global shared memory". The result of a simulation of accelerating computer tomography algebraic reconstruction on multi-GPU demonstrates effectiveness of this approach. DOI: http://dx.doi.org/10.11591/telkomnika.v11i8.3038